Analisis Penerapan Modal Intelektual Pada Lembaga Keuangan Syariah (Studi Kasus BMT Gontor) - Husni, Indra Sholeh; Afif, Mufti; Addin, Musyaffa (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
The development of Islamic financial institutions in Indonesia demands enhanced competitiveness and performance through the optimization of available resources, including intellectual capital. This study aims to analyze the implementation of intellectual capital at Baitul Maal wat Tamwil (BMT) Gontor and evaluate its contribution to the organization’s performance improvement. A qualitative case study method was employed, utilizing in-depth interviews with BMT Gontor’s staff and management. The findings reveal that intellectual capital—which includes human capital, structural capital, and relational capital—has been effectively applied across all organizational levels. This implementation has had a positive impact on operational efficiency, faster decision-making, and service innovation. Moreover, the structured and continuous management of intellectual capital has strengthened BMT Gontor’s position as a reliable and competitive Islamic financial institution. The study concludes that intellectual capital is a strategic asset that significantly contributes to the success and sustainability of the organization.